Den moderne romans middelalderlige rødder - Bruhn, Jørgen (K&K - Kultur og Klasse, 2007)
The Medieval Roots of the Modern Novel In this article, Jørgen Bruhn has a double target for his investigations. Firstly, he aims at distinguishing between two different historical models for the novel genre: on the one hand, a ‘short’ history which claims that the modern novel was born in the Renaissance. A ‘long’ history, on the other hand, asserts that the novel has a history going back not only to the middle ages but even antiquity. M.M. Bakhtin is a main contributor to a ‘long’ history of the novel, and in order to justify the use of Bakhtinian ideas in the study of the medieval romance, Bruhn points to the crucial insights of Bakhtin’s texts regarding the medieval romance. In the second part of the article Bruhn goes further into a specific romance, Chrétien de Troyes’ Erec et Enide from the second half of the 12th century. There are strong elements of metafictionality, a budding understanding of the social determination of human existence and a clear and sophisticated reflection on generic conventions, including the medieval tendency of referring to oneself as only a mediator or scribe. Therefore, Bruhn concludes that Chrétien’s romances in many ways can be characterized as an early expression of what Bakhtin usually called novelness, and that Chrétien himself must be characterized a modern »author«.